The field of capital mobility and the gravitation of profit rates (USA 1948-2000) - Dumenil, Gerard; Levy, Dominique (2002)
This study is devoted to the empirical investigation of the gravitation of profit rates among industries around a single value in the United States since World War II. The framework of analysis is that developed by classical economists and Marx, and used in many contemporary studies. The gravitation of profit rates around a single value results from the mobility of capital seeking a maximum profit rate. A preliminary concern is to determine the field in which this mobility of capital is likely to occur. A segment of the economy is excluded because of its deficient capitalist nature. After this exclusion, it appears that the profit rates of industries do tend to gravitate around a common value. An important finding of this study is that this gravitation is not observable within a subset of industries, such as Transportation or Public Utilities, which utilize very large amounts of fixed capital in comparison to employment or output. - Reproduced.
Keywords: Profits - United States; Profits